Changes and tracking of bone mineral density in late adolescence: the Tromsø Study, Fit Futures - Nilsen, Ole Andreas; Ahmed, Luai A.; Winther, Anne; Christoffersen, Tore; Furberg, Anne-Sofie; Grimnes, Guri; Dennison, Elaine; Emaus, Nina (Archives of Osteoporosis, 2017)
Summary : Areal bone mineral density (aBMD) predicts future fracture risk. This study explores the development of aBMD and associated factors in Norwegian adolescents. Our results indicate a high degree of tracking of aBMD levels in adolescence. Anthropometric measures and lifestyle factors were associated with deviation from tracking. Purpose : Norway has one of the highest reported incidences of hip fractures. Maximization of peak bone mass may reduce future fracture risk. The main aims of this study were to describe changes in bone mineral levels over 2 years in Norwegian adolescents aged 15–17 years at baseline, to examine the degree of tracking of aBMD during this period, and to identify baseline predictors associated with positive deviation from tracking. Methods : In 2010–2011, all first year upper secondary school students in Tromsø were invited to the Fit Futures study and 1038 adolescents (93%) attended. We measured femoral neck (FN), total hip (TH), and total body (TB) aBMD as g/cm2 by DXA. Two years later, in 2012–2013, we invited all participants to a follow-up survey, providing 688 repeated measures of aBMD. Results : aBMD increased significantly (p < 0.05) at all skeletal sites in both sexes. Mean annual percentage increase for FN, TH, and TB was 0.3, 0.5, and 0.8 in girls and 1.5, 1.0, and 2.0 in boys, respectively (p < 0.05). There was a high degree of tracking of aBMD levels over 2 years. In girls, several lifestyle factors predicted a positive deviation from tracking, whereas anthropometric measures appeared influential in boys. Baseline z-score was associated with lower odds of upwards drift in both sexes. Conclusions : Our results support previous findings on aBMD development in adolescence and indicate strong tracking over 2 years of follow-up. Baseline anthropometry and lifestyle factors appeared to alter tracking, but not consistently across sex and skeletal sites.